O mito da beleza e a psicanálise: análise dos padrões de beleza em interferência ao feminino - Araujo, Maria-Letícia di Rodrigues (Universidade Federal do Tocantins, 2023)
The present work aimed to investigate the subjective implications of beauty standards in interference with the feminine, starting from the concerns of Naomi Wolf's work, "The beauty myth" and the psychoanalytic theories about femininity. As a method, a bibliographical study and field research were used. As an instrument, a semi-structured interview was used based on a previously established script. Three women aged 25, 35 and 41 years old participated in this study. From the awakened reflections, it was understood that social media contribute to the construction of the image of an ideal body self, based on an unattainable standard. This fact, in turn, leads women in an incessant quest to achieve this ideal. Finally, it was observed that the impositions of a type of beauty cause psychic suffering in women who, according to the reports, see it as impossible to be chosen as an object of love for the other, also demonstrating fear of aging as a consequence of invisibility and segregation Social. Therefore, beauty is placed as a symbolic construct to answer the enigma of femininity. Being read as an intrinsic characteristic of the female gender, beauty is used as a capitalist tool to encourage the consumption of products and make women products to be consumed.